IV Immunoglobin Therapy in Dermatomyositis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Improved strength and functional abilities following IV immunoglobulin treatment for chronic dermatomyositis is reported in two children from the University of Mississippi Medical Center, Jackson, MS.